Over Fotografen : Twaalf gesprekken met Belgische fotografen - Bekkers, Ludo (S.l. : Dienst Pers en Publikaties van de BRT, 1984)
Dries, Antoon ; Tas, Filip ; Grooteclaes, Hubert ; Ausloos, Paul ; De Mulder, Walter ; Vercheval, Georges ; Selleslaghs, Herman ; Gruyaert, Harry ; Carez, Christian ; Hansen, Ben ; Vinck, John ; Cordier, Pierre
boek